Statystyczna analiza potencjału ekonomiczno-finansowego spółek notowanych na Giełdzie Papierów Wartościowych w Warszawie - Łuniewska, Małgorzata; Tarczyński, Waldemar (Statistical Analysis of Financial and Economic Potential of Companies Quoted on the Warsaw Stock Exchange, 2007)
The Warsaw Stock Exchange is considered a barometer of economy. The most important Polish companies are listed there, which creates a picture of national economy. Financial and economic potential in such companies is a very important issue. Financial and economic condition of companies, measured by liquidity, profitability, liabilities and management efficiency is a base of financial and economic potential. Generally it is multidimensional issue, which could be analyzed using some multivariate statistical methods. One of these methods is synthetic measure of development (TMAI). Utilizing this measure to evaluate potential of branches of stocks on WSE is proposed in the paper. Statistical analysis of financial and economic ratios in branches was carried out and synthetic measure of development was constructed. The averages of TMAI for branches were presented, which allowed the assessment of financial and economic potential.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 331-342